Unidirectional theta replication of the structurally stable Enterococcus faecalis plasmid pAM beta 1. - Bruand, C (1991)
Numerous bacterial replicons remain poorly characterized due to difficulties in localization of the replication origin. We have circumvented this problem in the characterization and fine mapping of the origin of plasmid pAM beta 1 by exploiting the Bacillus subtilis termination signal, terC. In terC-containing derivatives, theta-form molecules with two invariant endpoints accumulate. The endpoints, which correspond to plasmid origin and terC, were mapped with single-nucleotide precision. Analysis of the replication intermediates of wild-type molecules by two-dimensional gel electrophoresis confirmed the location of the plasmid origin. Our results demonstrate that pAM beta 1 replication proceeds unidirectionally by a theta mechanism. This work confirms the use of termination signals to localize origins, suggests that termination in B. subtilis occurs by a mechanism similar to that of Escherichia coli and establishes that in addition to rolling circle replicating plasmids, Gram positive bacteria harbour plasmids which replicate by a theta mechanism.